The belligerent occupation is a reason for the right to humanitarian asylum - Saighi, Ouided (Journal of Human Sciences, 2023)
Peace does not mean the end of conflicts, but requires full respect for the principles of sovereignty, fundamental freedoms and human rights, dialogue and cooperation between peoples and multiple cultures, and the rejection of cultural force and its use, in application of the famous saying (live and let others live), so that opposite peace comes violence and wars as a concept of hostility and division, which poses the problem of knowing if this peace can go beyond its concept to seek to end or attenuate the gravity of the violence in progress, which we discover in the legal framework of the cases of conflicts, wars and belligerent occupation in some countries.